The relationship between professional self-concept and responsibility with nursing students’ clinical performance of Bushehr University of Medical Sciences - Niloufar Hajipour; Shahnaz Pouladi; Marzieh Mahmoudi; Sherafat Akaberian (Journal of Education and Health Promotion)
BACKGROUND: The clinical performance of nurses is a challenge to the healthcare system, influenced by various factors. It is necessary to investigate the effective factors related to this concept to achieve proper clinical performance during education. This study was conducted to determine the relationship between professional self-concept, responsibility, and the clinical performance of nursing students at Bushehr University of Medical Sciences. MATERIALS AND METHODS: This descriptive-analytical study was conducted on 170 nursing students of Bushehr University of Medical Sciences in 2023, using the census method. A demographic information form, Cowin’s Nurses’ Self-Concept Questionnaire, Responsibility Among Bachelor Degree Nursing Students Scale (RABDNSS), and the Six-Dimension Scale of Nursing Performance were used to collect the data. Mean, standard deviation, and frequency tables were used to describe the data. Data analysis was done using Pearson’s correlation coefficient, independent t test, one-way analysis of variance, and linear regression. RESULTS: The mean professional self-concept was 162.15 ± 29.02, and the mean professional responsibility was 175.22 ± 27.13. The mean clinical performance of the nursing students was 157.84 ± 19.63. There was a positive and significant relationship between all dimensions of professional self-concept and all dimensions of clinical performance, and also between all dimensions of professional responsibility and all dimensions of clinical performance (P < 0.05). CONCLUSION: Nursing managers and policymakers should design educational programs based on professional nursing values to promote professional self-concept and responsibility to ensure the quality of clinical performance of future nurses.